AN ANALYSIS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS’ COMPETENCE IN THE IMPLEMENTATION OF THE MERDEKA CURRICULUM IN PRIMARY SCHOOLS - Fadli, Ihsan Nur; Rahmawati, Ervina; Azzahra, Nasywa; Aisyah, Siti; Afriantoni (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the competence of Islamic Religious Education (IRE) teachers in implementing the Merdeka Curriculum in primary schools, with a specific focus on SD IT Nurul Iman Palembang. Employing a qualitative approach with a case study design, data were collected through observation, interviews, and documentation. The findings reveal that IRE teachers possess a good conceptual understanding of the Merdeka Curriculum. However, they encounter several challenges, including difficulties in integrating religious content with interdisciplinary themes, the complexity of curriculum textbooks, and the practical application of teaching modules and scientific approaches. To address these issues, teachers employ collaborative strategies, adapt instructional methods, and engage in continuous reflection. These efforts are essential to ensure the effective implementation of the Merdeka Curriculum and to foster students' competence in facing 21st-century challenges. Penelitian ini bertujuan untuk menganalisis kompetensi guru Pendidikan Agama Islam (PAI) dalam mengimplementasikan Kurikulum Merdeka di sekolah dasar, dengan fokus pada SD IT Nurul Iman Palembang. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kasus, melalui teknik pengumpulan data berupa observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa guru PAI memiliki pemahaman konseptual yang baik terhadap Kurikulum Merdeka. Namun, mereka menghadapi beberapa tantangan, seperti kesulitan dalam mengintegrasikan konten keagamaan dengan tema-tema lintas disiplin, kompleksitas buku ajar kurikulum, serta penerapan modul ajar dan pendekatan saintifik. Untuk mengatasi tantangan tersebut, guru menerapkan strategi kolaboratif, menyesuaikan metode pembelajaran, dan melakukan refleksi secara berkala. Upaya ini penting dalam memastikan implementasi Kurikulum Merdeka berjalan efektif dan mampu membentuk siswa yang kompeten dalam menghadapi tantangan abad ke-21.